“Enfermedad pélvica inflamatoria, embarazo ectópico previo y antecedente de cirugía tubárica como factores de riesgo de embarazo ectópico” Servicio de Ginecología del Hospital Regional Docente de Trujillo, 2000-2015 - Nuñez Acevedo, Edwars Salomón (2019)
ABSTRACT Objective: To evaluate whether pelvic inflammatory disease, previous ectopic pregnancy and previous pelvic surgery are risk factors for the development of ectopic pregnancy. Methods: Observational, retrospective and analytic case-control study. Two groups were included: the cases group (90 patients) and the control group (180) for each factor in the Hospital Regional of Trujillo from 2000 to 2015. Bivariate descriptive statistical analysis was carried out using the Pearson chi-square test, p < 0.05, with odds ratio (OR) and 95% confidence interval (95% CI). Results: The study revealed that the risk of ectopic pregnancy (EP) was associated with the traditional risk factors including pelvic inflammatory disease (PID) (OR = 6.5, 95 % CI: 3.08 - 14.05), previous EP (OR = 4.29, 95 % CI: 1.3 - 14.6), previous adnexal surgery (OR = 1.2, 95 % CI: 0.28 - 5.16) and PID and previous EP (OR = 2.7, 95 % CI: 0.6 - 12.5). Conclusions: Pelvic inflammatory disease and previous ectopic pregnancy are risk factors of developing ectopic pregnancy.